Correlates of abortions and condom use among high risk women attending an STD clinic in St. Petersburg, Russia. - Abdala, Nadia; Zhan, Weihai; Shaboltas, Alla V; Skochilov, Roman V; Kozlov, Andrei P; Krasnoselskikh, Tatiana V (Reproductive health, 2011)
Many women in Russia rely on abortion as a primary birth control method. Although refusal to use contraceptives, including condoms, may undermine public health efforts to decrease HIV sexual risk behaviors, few studies have investigated the risk factors associated with abortion among women at high risk for HIV. This study sought to identify the correlates of abortions and of lack of condom use among high risk STD clinic patients in St Petersburg Russia.
Keywords: Abortion, Induced; Adolescent; Adult; Alcohol Drinking; Alcoholism; Ambulatory Care Facilities; Condoms; Epidemiologic Methods; Female; HIV Infections; Humans; Middle Aged; Pregnancy; Risk-Taking; Russia; Sexual Behavior; Socioeconomic Factors; Unsafe Sex; Young Adult